Derivative Proportional – Integral Controller Using Nelder-Mead Optimization for Glycerine Purification Heating Process - Janin, Zuriati; Mad Kaidi, Hazilah; Ahmad, Robiah; Khan, Sheroz (International Journal of Integrated Engineering, 2020)
It is important to purify the crude glycerine before to convert them into value-added products. Such dark colored crude have high free fatty acid content that can be removed via heating process. This paper focuses mainly on the heating control system, which has contributed to the improvement of the glycerine purification process system. The design of Derivative Proportional – Integral controller for the glycerine temperature control loop system could demonstrate some improvement of the glycerine heating process control response in term of process settling time and percent overshoot. Derivative Proportional – Integral is a proposed controller where Proportional and Derivative control actions operate on process variables rather than error signals. Meanwhile, the integral mode is connected to the forward path where the error signal is used as an input to the control mode. The output of the two control modes is then subtracted to drive the process. The Derivative Proportional – Integral controller was designed using the Nelder-Mead optimization algorithm with objective function of the Integral Time Absolute Error criteria calculated using Simpson’s one-third rule. The control performance of the proposed controller was analyzed by comparing the rise time, percent overshoot and settling time of the response with that of the conventional PID controller. The simulation results show that the Nelder-Mead optimization algorithm can be used and can produce a good control system with zero percent overshoot and shorter heating time compared to the achievements of the PID control system. In addition, the robustness test of the controller has shown that the proposed control system can effectively detect changes in the operating temperature. The control performance shown by the proposed controller is excellent. The Derivative Proportional – Integral control system designed based on optimization algorithm techniques can improve the performance of the glycerine purification process heating system to meet the purified glycerine requirements.